Foundation-sponsored networks: Brokerage roles of higher education intermediary organizations - Nabih Haddad (Arizona State University, 2020)
Philanthropic foundations are influential policy entrepreneurs in higher education, advocating new ideas, engaging in collaborative activities, and seeding research to inform the decision-making process. Despite occupying this role, the higher education literature has yet to examine how philanthropic foundations promote ideas between entities or how shared granting relationships are used to distribute and exchange information. By utilizing several sources of data, including in-depth interviews and an original dataset of postsecondary grants, and by applying social network concepts, this study explores the strategies educational funders use to disseminate ideas and promote information exchange. This study found that major foundations are not only taking on an advocacy-oriented role within their communication strategies, but they are also facilitating information sharing among intermediaries based on mutual granting relationships and shared agendas. Furthermore, the most impactful grantees are those who cross sectoral boundaries, such as advocacy nonprofits, think tanks, membership associations, and government agencies.